Agrofuels and transgenic crops: a couple that promotes the loss of food sovereignty - Espinosa, Milena (2013)
In order to approach to understanding the threat agrofuels and transgenic crops pose to food sovereignty, this paper revises some statements in relation to the dynamics related to these proposals and the socio–environmental conflicts they generate. Thus, firstly,some key concepts are defined; then, a general revision of the agrofuel production and transgenic expansion context is made, pointing out the perspectives and risks of this couple; next, the agroenergy model effects on food sovereignty are briefly studied inLatin America through the case of Argentina, projected as an important agroenergy producer with large areas of land to cultivate transgenic soy for export; finally, some conclusions are presented: agrofuel production and transgenic crops have a negative impact on peasants and consumers because of the import of food, the increase of foodprices, the dependence on external agricultural inputs, land conflicts and the loss of agricultural diversity, in the end the loss of food sovereignty.